2021
DOI: 10.3389/fonc.2021.628613
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Propranolol Reduces Biomarkers of Proliferation in Gastric Cancer

Abstract: Gastric cancer has one of the highest mortality rate in the world, but the treatment is still limited. Building on previous studies, mechanistic studies on propranolol in gastric cancer mice models and gastric cancer patients were performed. Propranolol inhibited the in vitro proliferation of gastric cancer cells in a time- and concentration-dependent manner. Consistent findings were observed in MFC tumors engrafted 615 mice, which were treated with propranolol at 10 mg/kg daily for 14 days. Propranolol inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Retrieved from https://app.biorender.com/biorender-templates. (64)(65)(66)(67)(68). Future studies may include PBS (or an isotype control antibody) to further confirm the feasibility of the proposed combination therapy in the MOC2 murine model.…”
Section: Discussionmentioning
confidence: 96%
“…Retrieved from https://app.biorender.com/biorender-templates. (64)(65)(66)(67)(68). Future studies may include PBS (or an isotype control antibody) to further confirm the feasibility of the proposed combination therapy in the MOC2 murine model.…”
Section: Discussionmentioning
confidence: 96%
“…In vitro studies, propranolol, the most commonly used nonselective-adrenergic antagonist, showed the ability to induce apoptosis, repress growth, suppress the expression of matrix metalloproteinases and vascular endothelial growth factor, and inhibit the migration of GC cells[ 38 , 39 ]. In a xenograft mouse model, propranolol decreased the levels of phosphorylated AKT, MEK, and ERK proteins and blocked depression-promoted neuroendocrine phenotypic transformation and lung metastasis of GC[ 31 , 40 , 41 ]. In patients with GC, treatment with propranolol for one week before surgery significantly inhibited the proliferation of cancer, as measured by Ki-67[ 40 ].…”
Section: Potential Perioperative Interventionsmentioning
confidence: 99%
“…In a xenograft mouse model, propranolol decreased the levels of phosphorylated AKT, MEK, and ERK proteins and blocked depression-promoted neuroendocrine phenotypic transformation and lung metastasis of GC[ 31 , 40 , 41 ]. In patients with GC, treatment with propranolol for one week before surgery significantly inhibited the proliferation of cancer, as measured by Ki-67[ 40 ]. In other cancer types, the anticancer ability of propranolol has also been found to be associated with enhanced antitumor immunity[ 42 , 43 ].…”
Section: Potential Perioperative Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that denervation exhibits considerable merit in preventing tumor progression, the potential side-effects may hinder its translation into clinical practice. On the other hand, pharmacological inhibition of neural receptors appears to be a reliable intervention that may be applied into clinical use [ 252 , 253 ]. Coinciding with the presumed tumor-facilitating role of β-AR signaling, epidemiological studies revealed that administration of β-blockers, such as propranolol, may reduce GI cancer risk [ 254 , 255 , 256 ].…”
Section: Intervention Of Neural Infiltration As Measurements Of Cance...mentioning
confidence: 99%